Atypical case of ruptured intracranial dermoid cyst - M, Nadiah; B, Norafida; AR, Ruwaida; MN, Mohamad Syafeeq Faeez; AR, Ezamin (The Journal of Health and Translational Medicine (JUMMEC), 2024)
An adult female with underlying Major Depressive Disorder presented with recurrent depressive episodes and altered behaviour. Plain CT and MRI showed right middle cranial fossa lesion with a typical CT and MRI features of ruptured dermoid cyst.Intracranial dermoid cysts are uncommon lesions with characteristic imaging appearances. They are rare, benign, congenital, slow-growing cystic lesions. On imaging, they are usually well-defined lobulated, midline masses that have fat density on CT and high signal intensity on T1-with variable signal onT2-weighted MR images, unlike intracranial lipomas, which follow fat density on all sequences. Rupture of intracranial dermoid cysts is a relatively uncommon phenomenon and characteristically associated with fat density material in the subarachnoid spaces, such as intraventricular fat-fluid levels or fat globules in the sulci. It can cause serious complications such as chemical meningitis, vasospasm, and cerebral infarction. MRI is a modality of choice to assess the extension of complications.